Analisis Penilaian Kinerja Terhadap Rasionalitas Dosen pada 114 Perguruan Tinggi Swasta (PTS) Wilayah Kopertis XIII Provinsi Aceh dengan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Munawir Munawir (KITA Institute, 2018)
This research aims to make a sort 104 University in Region XIII Kopertis Aceh Province with the method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) against the ratio of lecturers and students. TOPSIS is one method that can be used to solve the problem of Fuzzy MADM. This research takes into account all thecriteria that support decision making in order to help speed up and facilitate the decision-making process and do a minimal quantity of perangkingan especially the lecturer at a college. Based on research results, calculation of TOPSIS begins with forming a decision matrix is normalized, then continued with a decision matrix weighting normalization. The step is done to determine the ideal solution matrix of positive and negative solution is ideal. The last stages of the method is to calculate the value of the preference of each alternative (Vi) in order to get the final results, the most high value Vi shows the best alternative. Based on the end result then sorted 25 Colleges(PTS) is Locality Kopertis XIII Aceh at its best.